2002
DOI: 10.1002/ep.670210209
|View full text |Cite
|
Sign up to set email alerts
|

American creosote site case study: Solidification/stabilization of dioxins, PCP, and creosote for $64 per cubic yard

Abstract: Solidifiication/Stabilization (S/S) is a low-cost remedialtechnology that has been used extensively for decades to treat soil contaminated with metals on Superfund sites. Increasingly, it is being used with success to remediate sites that contain higher molecular weight organic compounds. This case study describes the development of S/S formations and their application to remediate the American Creosote Superfund Site in Jackson, Tennessee. The U S . EPA National Risk Management Research Laboratory conducted s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Although S-S treatment of inorganic contaminants has been practiced for many years, and there are many studies on the application of S-S technology in the remediation of inorganic contaminants, studies on the use of S-S with organic contaminants are comparatively less extensive (Al-Tabbaa and Rose Gitipour et al 1997;Hwang and Batchelor 2002;Bates et al 2002;Sora et al 2002;Yilmaz et al 2003;Botta et al 2004). The suitability of S-S treatment for organic contaminants has been reviewed by Pollard et al (1991), and a recent extensive review of this technology by Bone et al (2004) is also available.…”
Section: Solidification-stabilization Of Organic Contaminantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although S-S treatment of inorganic contaminants has been practiced for many years, and there are many studies on the application of S-S technology in the remediation of inorganic contaminants, studies on the use of S-S with organic contaminants are comparatively less extensive (Al-Tabbaa and Rose Gitipour et al 1997;Hwang and Batchelor 2002;Bates et al 2002;Sora et al 2002;Yilmaz et al 2003;Botta et al 2004). The suitability of S-S treatment for organic contaminants has been reviewed by Pollard et al (1991), and a recent extensive review of this technology by Bone et al (2004) is also available.…”
Section: Solidification-stabilization Of Organic Contaminantsmentioning
confidence: 99%
“…The result showed that a maximum of about 75% of 2-MCA was released in the leachate solution, which indicates that the treatment is not suitable for that compound without using any adsorbent. Bates et al (2002) reported the results of S-S treatment of various organic contaminants, including dioxins, Table 8. Selected results of the ACW treatability study (Bates et al 2002 pentachlorophenol (PCP), and creosote, using cement formulations containing activated carbon or other proprietary reagents at the American Creosote site (ACW site) in Jackson, Tennessee.…”
Section: Direct Immobilization Of Organic Contaminantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the USEPA conducted the site assessment and its subsequent remedial operation, which took place in 1999, after the removal of the excess water and creosote from the site. The remaining contaminated soil was treated by ex situ S/S to a depth of 1.5m, using a formulation of 5 % Portland cement, 4.5 % fly ash and 1.3 % powdered activated carbon (percentage by weight of untreated soil) (Bates et al, 2002). The treated soils were compacted and covered with a geosynthetic clay liner (GCL), capped with 0.6 m of clean fill and 0.12 m of topsoil (Bates et a/., 2002).…”
Section: Site Descriptionmentioning
confidence: 99%
“…The remaining contaminated soil was treated by ex situ S/S to a depth of 1.5m, using a formulation of 5 % Portland cement, 4.5 % fly ash and 1.3 % powdered activated carbon (percentage by weight of untreated soil) (Bates et al, 2002). The treated soils were compacted and covered with a geosynthetic clay liner (GCL), capped with 0.6 m of clean fill and 0.12 m of topsoil (Bates et a/., 2002). The last stage of the remedial operation was seeding with grass, to improve the water drainage, and the installation of protective fencing to restrict the access to the site.…”
Section: Site Descriptionmentioning
confidence: 99%